Multimedia Content Analysis Theory and Applications - Divakaran, Ajay.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2009)
Multimedia Content Analysis: Theory and Applications covers the state of the art of multimedia content analysis in a tutorial fashion and provides a plan for future research. It includes unique coverage of multimedia content analysis based products described by pioneers in the field, and provides valuable perspective on the feasibility of state of the art techniques, as well as opportunities for the future. It also addresses the experiential aspect of multimedia content analysis. The material discusses multimedia content analysis in three broad sections, theory, human interaction with multimedia, and commercial products. The theory section reviews multimedia content analysis tools used to derive higher-level semantics from low-level audio and video features and covers the state of the art in temporal video segmentation using unsupervised and supervised techniques. The human interaction section describes techniques for incorporating the human perception of multimedia into analysis. The product section describes the world$1 (Bs first products based on multimedia content analysis. Multimedia Content Analysis: Theory and Applications serves as an excellent introduction to the field with every chapter presented in a self-contained manner. The contributing authors are leaders in the field who have defined and extended the state of the art.s
Context Extraction Through Audio Signal Analysis -- Extracting Semantics from Multimedia Content: Challenges and Solutions -- Broadcast Video Content Segmentation by Supervised Learning -- Audio Content Discovery: An Unsupervised Approach -- Capturing Text Semantics for Concept Detection in News Video -- High-Level Feature Detection from Video in TRECVid: A 5-Year Retrospective of Achievements -- Experiential Sampling for Object Detection in Video -- Experiential Media Systems #x2013; The Biofeedback Project -- Assessing the Usability of Video Browsing and Summarization Techniques -- Multimedia Analysis for Content Identification -- Sports Video Analysis: From Semantics to Tactics -- Video Fire Detection #x2013; Techniques and Applications in the Fire Industry -- Automatic Home Video Editing -- A Video Browsing enabled Personal Video Recorder.
Keywords: Computer science; Multimedia information systems; Image processing; Application software; Electrical engineering; Computer Science; Computer Applications; Signal, Image and Speech Processing; Image Processing and Computer Vision; Electrical Engineering; Multimedia Information Systems; Electronic books